Conceptual Metaphors in Visual Language The Graphic Novel City of Glass - Shiloh, Ilana (Research in Language, 2023)
The paper explores the use and impact of conceptual metaphors in the graphic novel City of Glass published by Paul Auster as a free-standing story in 1985. Two years later Auster turned it into the first part of The New York Trilogy, which has since become one of the most iconic works of postmodern fiction. Artists Paul Karasik and David Mazzucchelli have adapted Auster’s novella into a graphic novel and their version figures on the list of the best comic books in the 20th century. The aim of this paper is to examine how the two artists’ use of conceptual metaphors has elicited the visual dimension of Auster’s novel, conveyed its philosophical ideas and enriched its emotional effect.